2016
DOI: 10.1007/s12035-016-9893-3
|View full text |Cite
|
Sign up to set email alerts
|

Inosine, an Endogenous Purine Nucleoside, Suppresses Immune Responses and Protects Mice from Experimental Autoimmune Encephalomyelitis: a Role for A2A Adenosine Receptor

Abstract: Multiple sclerosis (MS) is a T cell autoimmune, inflammatory, and demyelinating disease of the central nervous system (CNS). Currently available therapies have partially effective actions and numerous side reactions. Inosine, an endogenous purine nucleoside, has immunomodulatory, neuroprotective, and analgesic properties. Herein, we evaluated the effect of inosine on the development and progression of experimental autoimmune encephalomyelitis (EAE), an experimental model of MS. Inosine (1 or 10 mg/kg, i.p.) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 66 publications
0
30
0
Order By: Relevance
“…54 Inosine has been shown to inhibit the production of IL-17 and -14 and to stimulate the release of adenosine A2A receptor (A2AR) in experimental autoimmune encephalomyelitis (EAE) models. 55 The role of increased linoleic acid and azelaic acid in AAU patients or inosine in HLA-B27 þ patients is unclear and deserves further study. It has been shown that short chain fatty acids (SCFAs) could promote the differentiation of Treg cells and are found to be implicated in several autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…54 Inosine has been shown to inhibit the production of IL-17 and -14 and to stimulate the release of adenosine A2A receptor (A2AR) in experimental autoimmune encephalomyelitis (EAE) models. 55 The role of increased linoleic acid and azelaic acid in AAU patients or inosine in HLA-B27 þ patients is unclear and deserves further study. It has been shown that short chain fatty acids (SCFAs) could promote the differentiation of Treg cells and are found to be implicated in several autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The information of effect allele, other allele, effect allele frequency, and sample size was also used to perform the MR analysis. SNPs were excluded from the MR analysis if their measured linkage disequilibrium had an r (Junqueira et al, 2017) greater than 0.01. We calculated the linkage disequilibrium using the CEU panel of the phase 3 data of the 1000 Genomes Project as the reference panel (The 1000 Genomes Project Consortium et al, 2015).…”
Section: Data Sources and Participantsmentioning
confidence: 99%
“…The etiology of MS is varied and not fully understood (Dobson and Giovannoni, 2019). As a potent scavenger of peroxynitrite, previous studies suggested that UA may play an important role in the development of MS (Liu et al, 2012;Junqueira et al, 2017). An updated meta-analysis using data from case-control studies showed that the serum UA level was lower in persons with MS than in healthy controls (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Under physiologic conditions, blood levels of inosine are increased by exercise and ingestion of certain foods (organ meats, beer, spinach) and exhibit diurnal variations. Over the past two decades, inosine has been shown to evoke significant improvements in motor function and visceral organ control in preclinical models of neurologic injury including SCI [19][20][21][22][23][24], stroke [25][26][27][28][29], traumatic brain injury [30], multiple sclerosis (MS) [31][32][33][34][35] and Parkinson's disease (PD) [36] through its ability to enhance the growth of axon collaterals from undamaged neurons. The basis of these beneficial effects stems from its antioxidant, anti-inflammatory, axogenic and neuroprotective properties (reviewed in [37]).…”
Section: Inosinementioning
confidence: 99%
“…As discussed below, inosine has been shown to bind directly to A 1 , A 2A and A 3 receptor subtypes [65][66][67][68], with affinities that are typically lower than that of adenosine. Although direct binding of inosine to A 2B has not been demonstrated, there is convincing evidence to suggest that inosine interacts functionally with all 4 adenosine receptor subtypes, to elicit a variety of effects depending on species and biological context [24,35,[68][69][70][71][72]. A summary of the diverse biological activities of inosine mediated by adenosine receptors is provided in Table 1.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%